2013
DOI: 10.1038/nature12271
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized and functional human liver from an iPSC-derived organ bud transplant

Abstract: A critical shortage of donor organs for treating end-stage organ failure highlights the urgent need for generating organs from human induced pluripotent stem cells (iPSCs). Despite many reports describing functional cell differentiation, no studies have succeeded in generating a three-dimensional vascularized organ such as liver. Here we show the generation of vascularized and functional human liver from human iPSCs by transplantation of liver buds created in vitro (iPSC-LBs). Specified hepatic cells (immature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
1,689
4
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,759 publications
(1,732 citation statements)
references
References 22 publications
24
1,689
4
15
Order By: Relevance
“…Three-dimensional culture techniques (Hoelting et al 2013) have enabled the generation of PSC-derived organoids (e.g., Preynat-Seauve et al 2009), allowing putative toxic compounds to be tested on tissues rather than on isolated cells. Finally, the use of PSCs to generate mice with humanized organs (e.g., Takebe et al 2013) provides new opportunities to represent physiological complexity. Collectively, we believe these constitute next-generation toxicity platforms.…”
mentioning
confidence: 99%
“…Three-dimensional culture techniques (Hoelting et al 2013) have enabled the generation of PSC-derived organoids (e.g., Preynat-Seauve et al 2009), allowing putative toxic compounds to be tested on tissues rather than on isolated cells. Finally, the use of PSCs to generate mice with humanized organs (e.g., Takebe et al 2013) provides new opportunities to represent physiological complexity. Collectively, we believe these constitute next-generation toxicity platforms.…”
mentioning
confidence: 99%
“…This landmark paper established a novel experimental paradigm for generating tissue organoids. Subsequent studies worldwide confirmed the generalizability of such approach to human stem cells, and produced organoids of a variety of organ types including colon,11 intestine,12 prostate,13, 14 fallopian tube,15 stomach,16 liver,17, 18 kidney,19 lung,20 and brain 8…”
Section: Organogenesis In a Dish: An Overviewmentioning
confidence: 92%
“…The virus preferentially infected and replicated in neural progenitors, induced cell death and decreased proliferation, leading to reduced neuronal cell layers and thus phenocopying the microencephaly caused by the virus in human fetuses (Dang et al, 2016;Garcez et al, 2016;Tang et al, 2016). Other organoids such as lung (Dye et al, 2015;Huang et al, 2013), liver Takebe et al, 2013), kidney (Takasato et al, 2015) and fallopian tube organoids (Kessler et al, 2015) may represent ideal models for infections of the respective tissues, such as respiratory virus, malaria parasite, biofilm-producing E. coli or Chlamydia infection, respectively. Future studies will use the unique features of organoids, such as the presence of specific cell types, to better understand infectious and inflammatory diseases.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%